2017
DOI: 10.1016/j.freeradbiomed.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin modulates endothelial permeability and monocyte transendothelial migration by affecting endothelial cell dynamics

Abstract: Curcumin is a phenolic compound that exhibits beneficial properties for cardiometabolic health. We previously showed that curcumin reduced the infiltration of immune cells into the vascular wall and prevented atherosclerosis development in mice. This study aimed to investigate the effect of curcumin on monocyte adhesion and transendothelial migration (TEM) and to decipher the underlying mechanisms of these actions. Human umbilical vein endothelial cells (HUVECs) were exposed to curcumin (0.5-1μM) for 3h prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 67 publications
0
27
0
Order By: Relevance
“…Using the in vitro model of TNF-α-activated EC, it was demonstrated that curcumin reduces the expression of VCAM-1, ICAM-1, E-selectin [63], fraktalkine and P-selectin [64], thereby inhibiting significantly monocyte adhesion through mechanisms involving the reduction of NADPH oxidase activation and consequently of the intracellular ROS production [64]. These results were confirmed in a recent study by Monfoulet et al, who demonstrated that curcumin pre-exposure reduces endothelial permeability and monocyte adhesion in both static and flow conditions [65]. In addition, most of the in vitro and in vivo studies confirm that curcumin administration determines the lowering of MCP-1 levels by downregulation of the MAPK and NF-κB signaling pathway [66][67][68].…”
Section: Introductionmentioning
confidence: 63%
“…Using the in vitro model of TNF-α-activated EC, it was demonstrated that curcumin reduces the expression of VCAM-1, ICAM-1, E-selectin [63], fraktalkine and P-selectin [64], thereby inhibiting significantly monocyte adhesion through mechanisms involving the reduction of NADPH oxidase activation and consequently of the intracellular ROS production [64]. These results were confirmed in a recent study by Monfoulet et al, who demonstrated that curcumin pre-exposure reduces endothelial permeability and monocyte adhesion in both static and flow conditions [65]. In addition, most of the in vitro and in vivo studies confirm that curcumin administration determines the lowering of MCP-1 levels by downregulation of the MAPK and NF-κB signaling pathway [66][67][68].…”
Section: Introductionmentioning
confidence: 63%
“…In porcine coronary artery, CUR blocked endothelial disfunction induced by homocysteine [127], which was detected as inhibited epithelial nitric oxide synthase expression and superoxide anion production, as well as blocked vasorelaxation. Improvements of endothelial function by pretreatment with CUR were confirmed in human umbilical vein endothelial cells, where reduced permeability and monocyte adhesion were detected [117,128]. In the same model cells, CUR blocked NF-κB activation induced by TNF-α and reduced ROS, adhesion of monocytes, phosphorylation of c-Jun N-terminal kinase p38, and STAT3 [129].…”
Section: Anti-atherosclerotic Effectmentioning
confidence: 84%
“…Interestingly, the abovementioned pro-inflammatory reactions and dysfunction in HAEC were reversed after Cur addition to PLLA. Cur also shows potent anti-inflammatory properties that could benefit vascular health (Monfoulet et al, 2017). Evidence indicates that Cur attenuates high glucose-induced inflammatory injury through the 3-kinase/protein kinase-NF-κb signaling pathway in rat thoracic aortic endothelial cells (Guo et al, 2015), and suppresses inflammation in the vascular endothelium by significantly reducing VCAM-1 and intercellular adhesion molecule 1 (ICAM-1).…”
Section: Discussionmentioning
confidence: 99%
“…These defects limit complete translation of Cur's in vitro benefits into clinical conditions. Nevertheless, several strategies have been tested to improve the bioavailability of Cur, including the use of natural enhancers of encapsulation systems, copolymeric micelles, polymeric nanoparticles, and liposomes and phytosomes (Monfoulet et al, 2017).…”
Section: Discussionmentioning
confidence: 99%